Identification of Bioactive Compounds by GC-MS Analysis and In vitro Antioxidant Activities of Debregeasia longifolia (Burm.f.) Wedd.: Medicinal Plant - Thirumoorthi, Suresh Kumar; Mani, Rama Prabha (International Journal of Pharmaceutical Investigation, 2026)
Objectives The study was aimed to investigate the presences of bioactive components by Debregeasia longifolia through Gas Chromatography-Mass Spectrometry (GC-MS) analysis and evaluate its in vitro free radical scavenging activity. Debregeasia longifolia is a member of the Urticaceae family that is used medicinally. Materials and Methods The methanolic extract was prepared by shade-drying the gathered leaves, grinding them into a fine powder, and then extracting them with methanol. The Debregeasia longfolia methanolic leaf extracts was analyzed for potential bioactive components using GC-MS (Agilent 8890) and evaluated for its in vitro free radical scavenging activity. Results A total of around fourteen bioactive components were identified during the GC-MS investigation, the current study focused on compounds with highest peak value and pharmacologic importance which include Phytol, Cyclobarbital, Hexadecanoic acid, methyl ester, Ipriflavone, Pinolenic acid, 2-Myristynoylglycinamide and some other components. The leaves were subjected to in vitro free radicles scavenging activity viz., DPPH, Nitric oxide, Hydroxyl, Total antioxidant activity, reducing power assay and all the assays shown strong antioxidant activity. Conclusion Debregeasia longifolia found to contain potent therapeutic components and related curative properties, hence suggested as a plant of phytopharmaceutical interest.
Keywords: Debregeasia longifolia leaves; Medicinal plant; GC-MS analysis; Phytocomponents; Free radical Scavenging assays